RELEVANSI ZIKRULLAH DALAM MENCEGAH TERORISME - Iskandar Iskandar (STAI Nusantara Kota Banda Aceh, 2026)
This paper is a response, through zikrullah, to the phenomenon of terrorism that continues to this day. Among Islamic mystics, zikrullah is a key element in purifying the mind of various reprehensible traits, yet its potential in the prevention of terrorism has not yet been explored in depth. A number of scholars have contributed to addressing guidelines on the prevention of terrorism, as exemplified by al-Qusyairy in his Risalah al-Qusyairiyah. In the context of psychological therapy, zikrullah is relevant in regulating brain waves to foster a tranquil state of mind, thereby freeing the individual from thoughts and behaviours associated with terrorism. The data in this paper is derived from qualitative data on zikrullah and quantitative data on the effect of zikrullah on brain waves, based on EEG samples from 10 subjects. Terrorism can occur in social interactions, within households, in various institutions, and in various locations. This is because perpetrators of terrorism are human beings.